Bimetallic CoxCuy-CAT-1 metal-organic frameworks for synergistic antibacterial contribution of photocatalytic-photothermal effect. Issue 3 (June 2022) - Tong, Haijian; Yang, Yuting; Shi, Fengyan; Ding, Mengna; Luo, Liulin; Miao, Yingchun; Huo, Yuning; Li, Hexing
Abstract: The serious threat of environmental microbial contamination to the health of human beings has drawn wide attentions. In this work, a series of bimetallic Cox Cuy -CAT-1 metal-organic frameworks (MOFs) with tunable Co/Cu molar ratio was prepared by one-pot route. All of Cox Cuy -CAT-1 samples were in the shape of nanorods with the strong interaction of Co and Cu centers. In addition to the less surface electronegativity and high specific surface area, which were beneficial for the contact of MOFs materials with bacteria, the bimetallic coordination in Cox Cuy -CAT-1 realized the synergistic contribution of photocatalytic-photothermal effect to the effective bacterial inactivation for E. coli, comparing to the photothermal and photocatalytic effect. The thermal effect and the intrinsic antibacterial nature of metal ions in MOFs were difficult to induce the efficient destroy of bacteria. The photocatalytic effect could not remain the stable antibacterial rate and realize the obvious mineralization effect via the photo-induced holes on Cox Cuy -CAT-1. However, the synergistic photocatalytic-photothermal effect could lead to the promoted photo-thermal conversion efficiency by the efficient visible-light absorption and electron separation/transfer, and the strong and stable photothermal effect simultaneously promoted the light absorption and electron transfer. As a result, the more efficient generation of photo-induced holes were beneficial for forming more ·OH radicals, and then ·OH radicals efficiently reacted with bacteria without the surface coverage in MOFs, leading to the stable antibacterial rate and highly effective mineralization of bacteria . This work showed the significance on the synergistic photocatalytic-photothermal contribution of bimetallic MOFs materials to the environmental sterilization in the future. Graphical Abstract: ga1 Highlights: Bimetallic Cox Cuy -CAT-1 MOFs was prepared with tunable Co/Cu molar ratio. Cox Cuy -CAT-1 realized synergistic contribution of photocatalytic-photothermal effect. Photothermal conversion and light absorption with electron transfer were mutually promoted. Stable inactivation and effective mineralization of E. coli were realized by ·OH radicals.